(3GdGSJOQGc Ydi CHj YeQ Hf YHO GdHQ GdMGaX aj cJGHg GdGSJjYGHs - (3EHQGgje Hf jMji Hf EHQGgje Hf SYjO, CHh ESMGb , GHf GdCejf, GdWdjWdi Ke GdbQWHi , J (B544 (3g`s; (3GHf YHO GdHQ , CHh YeQ jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj,J (B463 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdMGaX Jbi GdOjf CHh YeQh YKeGf Hf YHO GdQMef GHf YKeGf YQa HGHf GdUdGM s
(3BNQgG (B:s
(3heG cGf ef bHd GdQLd abGd GdJHi Udi Gddg Ydjg hSde Pdc GdQLd jHYK CeI hMOg dPdc GdebJhd (B" (3BNQ RjGOGJ Nda ced GdcJGH s
(3GdcJGH ef QhGjI GdMGaX CHj GdbGSe Nda Hf YHO Gdedc Hf eSYhO GdeYQha HGHf GdbQWHi Yfgs
(3hRGO ajg RjGOGJ cKjQI hYdi GdfSNI SeGYGJs
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B315s
Keywords: (3GdJGQjNs